The Effect of Combination Therapy with Rituximab and Intravenous Immunoglobulin on the Progression of Chronic Antibody Mediated Rejection in Renal Transplant Recipients. (29th January 2014) - An, Gun Hee; Yun, Jintak; Hong, Yu Ah; Khvan, Marina; Chung, Byung Ha; Choi, Bum Soon; Park, Cheol Whee; Choi, Yeong Jin; Kim, Yong-Soo; Yang, Chul Woo
Abstract : The treatment for chronic active antibody-mediated rejection (CAMR) remains controversial. We investigated the efficacy of rituximab (RTX) and intravenous immunoglobulin (IVIg) for CAMR. Eighteen patients with CAMR were treated with RTX (375 mg/m 2 ) and IVIg (0.4 g/kg) for 4 days. The efficacy of RTX/IVIg combination therapy (RIT) was assessed by decline in estimated glomerular filtration rate per month (ΔeGFR) before and after RIT. Patients were divided into responder and nonresponder groups based on decrease and no decrease in ΔeGFR, respectively, and their clinical and histological characteristics were compared. Response rate to RIT was 66.7% (12/18), and overall ΔeGFR decreased significantly to 0.4 ± 1.7  mL·min −1 ·1.73 m −2 per month 6 months after RIT compared to that observed 6 months before RIT (1.8 ± 1.0, P < 0.05 ). Clinical and histological features between the 12 responders and the 6 nonresponders were not significantly different, but nonresponders had a significantly higher proteinuria levels at the time of RIT (2.5 ± 2.5 versus 7.0 ± 3.5 protein/creatinine (g/g), P < 0.001 ). The effect of the RIT on ΔeGFR had dissipated in all patients by 1 year post-RIT. Thus, RIT delayed CAMR progression, and baseline proteinuria level was a prognostic factor for response to RIT.